2009
DOI: 10.1063/1.3120549
|View full text |Cite
|
Sign up to set email alerts
|

Twist defect in an imprinted cholesteric elastomer

Abstract: We have found that a chiral twist defect inserted in a cholesteric elastomer gives rise to circularly polarized localized modes of both handedness. This defect enhances the resonant mode amplitude whose handedness is opposite to that of the cholesteric helix for high cross-linked density, whereas for low cross-linked density, the same mode is decoupled with the defect and thus the resonant mode disappears. Finally, the resonant mode of the same handedness as the elastomer helix is maintained for both high and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…The simplest way of obtaining the proposed structure to use polymer cholesteric elastomers [41] instead of conventional CLCs. Schmidtke et al [27] and Castro-Garay et al [42] experimentally observed the photonic defect modes induced by the twist structural defect in such cholesteric materials. The twist defect can be formed by rotation of one part of the elastomer relative to the other part around the helix axis so that the director variation continuity is broken.…”
Section: Description Of the Modelmentioning
confidence: 99%
“…The simplest way of obtaining the proposed structure to use polymer cholesteric elastomers [41] instead of conventional CLCs. Schmidtke et al [27] and Castro-Garay et al [42] experimentally observed the photonic defect modes induced by the twist structural defect in such cholesteric materials. The twist defect can be formed by rotation of one part of the elastomer relative to the other part around the helix axis so that the director variation continuity is broken.…”
Section: Description Of the Modelmentioning
confidence: 99%
“…The system might function as a filter with chemically controlled bandwidth and reflectance. Still on the subject of distorted elastomers, it has been suggested that a chiral twist defect inserted in a cholesteric elastomer gives rise to CP localized modes of both handedness 223. This defect enhances the resonant mode amplitude whose the handedness is opposite that of the helix for high crosslinking density (this parameter is related to the chiral parameter order), whereas the same mode is decoupled with the defect and the resonant mode disappears for low density.…”
Section: Going Beyond the Reflectance Limitmentioning
confidence: 99%
“…To broaden the bandwidth, different methods have been employed such as forming a pitch gradient 9,10 or creating a non-uniform pitch distribution. 11,12 In recent years, many theoretical studies [13][14][15] and experimental methods [16][17][18] have been developed to achieve a broadband reection. The rst example was introduced by D. J. Broer in 1995, and he obtained a broadband reection of the entire visible spectrum by introducing a pitch gradient in the cholesteric polymer network via UV-induced polymerization of chiral LC diacrylate/nematic monoacrylate/photoinitiator blends.…”
Section: Introductionmentioning
confidence: 99%